Essential Cataloguing : the Basics. - Bowman, J. H. (Facet Publishing, 2013)
Designed as a simple companion to ""AACR2"", this book covers descriptive cataloguing for library school students, beginning cataloguers and information professionals. It is fully cross-referenced to ""AACR2"", taking into account the 2002 revisions, and also includes MARC21 coding and examples